Creating a Digital Information Map in Hanura Village, Pesawaran Regency - Afwan, Nur; Rosmiati, Viona; Herlinawati, Fegy; Mahesa, Ages; Zaidani, Aura Husnaini Putri; Baysella, Zahira Sandra; Widiarso, Yosef (Indonesian Journal of Community Services Cel, 2025)
This community service activity focuses on the creation of a digital information map in Hanura Village, which aims to improve the management of infrastructure, agriculture, natural resources, and spatial planning. It also helps in disaster management, economic development, and better public services. This map not only increases government transparency but can also be used as a basis for the development of innovative applications. Thus, the creation of a digital information map is an important tool in the planning and management of the Hanura Village area and improves the quality of life of the local community. The creation of this information map is an important step in spatial data management in Hanura Village because it helps in resource management, disaster risk mitigation, economic development, increases government transparency, and supports better decision-making related to regional planning. The method used involved field surveys and digital mapping technology in Hanura Village, on July 1-20, 2023. The results of this community service activity show the implementation of an information map that successfully integrates diverse data, such as infrastructure, agricultural land, public assets, as well as geographic and demographic characteristics. The discussion includes the significance of information maps in supporting sustainable regional planning and community participation in the decision-making process. The importance of information maps as an effective tool in embracing data diversity to help create a better understanding of village dynamics and support better informed decision-making.